Acceptance and Intentions of Using Dynamic Geometry Software by Pre-Service Primary School Teachers - Steven Van Vaerenbergh; Adrián Pérez-Suay; Pascual D. Diago (MDPI AG, 2023)
In this paper, we empirically verify the validity of the extended Technology Acceptance Model (TAM) for the use of Dynamic Geometry Software (DGS) in teaching geometry, as proposed by Pittalis. The model includes the notion of "perceived pedagogical-learning fit" in addition to the traditional belief and attitude variables of TAM. We employ a structural equation modeling approach to capture the relationships between the different latent constructs. With a sample of 135 pre-service primary school teachers as participants, our study provides valuable insights into the factors influencing the adoption of DGS in geometry teaching. The results reveal that the extended TAM serves as a suitable framework to evaluate the intentions of teachers to use DGS in teaching geometry. However, we also observe some discrepancies in the predictive power of various latent factors when compared to the original study. These findings not only contribute to our understanding of the factors affecting the adoption of DGS in geometry teaching but also provide valuable insights for future research and practice.